Association between Consumption of Fluoroquinolones and Carbapenems and Their Resistance Rates in Pseudomonas aeruginosa in Argentina - Boni, Silvia; Marin, Gustavo H.; Campaña, Laura; Marin, Lupe; Risso-Patrón, Soledad; Marin, Gina; Gabriel, Fernanda; Corso, Alejandra; Garay, Valeria; Limeres, Manuel (Interdisciplinary Perspectives on Infectious Diseases, 2022)
Background. Irrational use of antimicrobials (ATMs) triggers microbial resistance (AMR) which has severe consequences for human health. ATM consumption varies among countries and within each territory. These data should be known, in order to perform local policies towards AMR reduction. This work aimed to expose the association of the level of consumption of carbapenems and fluoroquinolones with their resistance rates in Pseudomonas aeruginosa in Argentina. Method. Consumption of antimicrobials was expressed by defined daily dose (DDD)/1000 inhabitants for each ATM during one year period, discriminating by each country region. Resistance of P. aeruginosa to carbapenems/fluoroquinolones groups was recorded. Consumption/resistance ratio “R” was calculated for each region of the country, comparing results with other countries. Results. P. aeruginosa resistance rate to fluoroquinolone (F) was 26.4% in blood samples and 29.7% in urine samples, whereas resistance rates to carbapenems (C) were 19.9 and 17.7% in blood and urine, respectively. Correlation between consumption and resistance was demonstrated for both antimicrobials (C : R = 0.58; p=0.003 and F : R = 0.77; p=0.0001). Great fluctuations of resistance levels were seen among regions within the country, always correlating resistance with areas in which a higher level of ATM consumption was detected. Conclusion. P. aeruginosa resistance to fluoroquinolone/carbapenems in Argentina directly correlated with antimicrobial consumption levels. A great heterogeneity in resistance profile was observed among areas where ATMs were widely used. Global data at the national level might mask local realities that require specific health policies in order to control the irrational use of ATMs.